Addressing the Role of the Family in Preventing Youth Gang Crime: The Case of Bangladesh - Uddin, Md. Helal; Muhammad, Saud Bin; Iqbal, Masud (Journal of Cultural Analysis and Social Change, 2025)
The main aim of this article is to explore the critical role of the family as a protective factor in preventing youth gang crime in Bangladesh. The family is a main building block in society and an integral part of human life. In recent years, youth gang crime has proliferated like an epidemic in society in Bangladesh. This study has been used a qualitative and library-based method and conducted an extensive review of scholarly literature. The study examines the influence of familial support and effective familial strategies of moral guidance, emotional support, and instilling religious teachings to counteract youth engaging in gangs and committing criminal activities. Moreover, the study investigates the influence of socio-economic crises within the family, social media, and violent activities in forming and recruiting youth into gang crimes. In addition, the study explores the role of religious values and extended families resisting and mitigating against youth aggressive behaviour and criminal activities. This article contributes on comprehending relationship between youth criminal behaviour and families in Bangladesh and proposes recommendations for bolstering familial measures.